Adolescence and beyond : family processes and development - Kerig, Patricia; Schulz, Marc S.; Hauser, Stuart T. (Oxford : Oxford University Press, 2012)
'While the period of transition from adolescence to adulthood has become a recent focus for developmental psychologists and child mental health practitioners, the full role of the family during this period is only beginning to be explored. Many compelling questions, of interest to anyone involved in adolescence research, remain unanswered. To what extent do family experiences influence the way one navigates through emerging adulthood? How do we begin to understand the interplay between adolescents' contexts and their development and well-being? Adolescence and Beyond: Family Processes and Development offers an accessible synthesis of research, theories, and perspectives on the family processes that contribute to development. Chapters from expert researchers cover a wide variety of topics surrounding the link between family processes and individual development, including adolescent romantic relationships, emotion regulation, resilience in contexts of risk, and socio-cultural and ethnic influences on development. Drawing on diverse research and methodological approaches that include direct family observations, interviews, and narrative analyses, this volume presents cutting-edge conceptual and empirical work on the key developmental tasks and challenges in the transition between adolescence and adulthood. Researchers, practitioners, and students in social, developmental, and clinical psychology--as well as those in social work, psychiatry, and pediatrics--will find this book an invaluable summary of important research on the link between family process and individual development'--
Includes bibliographical references and index.
Keywords: Adolescence; Adolescent psychology; Teenagers -- Family relationships; Teenagers -- Sexual behavior